UPAYA PENINGKATAN KEMAMPUAN MEMBACA Al QUR’AN INDAH DENGAN METODE TILAWATI - Ummi Hani’ Farihah (Atthiflah: Journal of Early Childhood Islamic Education, 2021)
Reading the Qur'an must pay attention to the rules that have include: Tajwid Science, Gharib science, Makharijul Letters, and able to understand and pronounce long or short readings. So, in the process of learning to read the Qur'an, these rules must be studied and understood properly because if the rules are not properly understood, then the recitation of the Qur'an also becomes false. Effective teaching means teaching that students can understand perfectly. In the science of education it is often also said that proper teaching is teaching that functions in students. "Functioning" means belonging to the student, the teaching shapes and influences his person. The Tilawati method is a method of learning the Qur'an with basic techniques talqin-taqlid (mimicking) like the Prophet Muhammad mimicking the reading of the Angel Gabriel. The process of learning the Tilawati Method, always focuses on the application of tajwid science theories properly and correctly according to the command of Allah SWT which requires the recitation of the Qur'an in tartil. This research uses quantitative research. Quantitative research is a research method based on the philosophy of positivism used to examine in a particular population or sample sampling techniques are generally done randomly, data collection using research instruments, quantitative data analysis / statistics with the aim to test established hypotheses. With a descriptive format is a study by collecting field data and analyzing and drawing conclusions from the data. The success of the Qur'anic learning strategy using the Tilawati method as an effort to improve the ability to read beautifully class XI Otkp 3 learners in SMK Negeri 2 Balikpapan, indicated by an increase in the learning process, namely readiness and liveliness during the qur'an learning process, also showed an increase in the final test score score of each cycle. This can be seen from the acquisition of scores presented through observations about the learning spirit of learners with readiness and liveliness in the learning process. Based on cycles 1 and 2, there is an increase in the ability to read beautifully in the material QS Al-Maidah; 48, An-Nisa':59 and At-Taubah:105 by students of class XI Otkp 3 at SMK Negeri 2 Balikpapan. Where in cycle 1 the average value of beautiful reading skills is achieved in the range of 69.95 while in cycle 2 the average value of beautiful reading skills using the Tilawati method is in the range reaching 82.38. Where it has reached the level of completion above 73% of student who have 21, namely with the KKM that has been determined is 73. With the increasing ability to read beautifully in the material QS Al-Maidah; 48, An-Nisa':59 and At-Taubah: 105 which has a positive impact, namely an increase in the final score above the completion value of at least KKM (73) the ability to read then learning the Qur'an using the Tilawati method is effectively applied in PAI learning.